Effect of alkaline-catalyzed in homogeneous reaction of biodiesel production from waste cooking oils using ultrasonic bath-cleaner - Mohd Syafiq, Salim (2008)
Many years of research have been done in order to find a new alternative renewable fuel such as biodiesel to replace the diesel fuel. Biodiesel was used instead of conventional diesel fuel because there is a highly concern and awareness for environmental protection and due to increase of the petroleum price. Hence the aimed of this research is to investigate the feasibility of waste cooking oils (WCOs) used as feedstock to produce biodiesel by alkaline-catalyzed process. The performance of alkaline-catalyzed such as sodium methoxide (NaOCH3) was investigated towards biodiesel yield and selectivity (methyl ester conversion) of product by using ultrasonic bath-cleaner. This transesterification process was conducted with a molar ratio of methanol-oils used fixed to (6:1). In order to obtain the optimum condition for biodiesel production, three stages of experiment with different parameter setting such as catalyst concentration (0.5 to 2.5 wt %), temperature (40 to 80°C) and reaction time (20 to 60 min) were performed through this transesterification process. The results indicated that, catalyst concentration was the major effects affecting biodiesel yield and methyl ester conversion. However, temperature and reaction time were related together in which the time required for reaction completion varied significantly with reaction temperature. The results showed that the optimum condition for biodiesel production can be achieved at catalyst concentration of 1.0 wt %. The temperature and reaction time was conducted at 60°C and 40 minutes which indicated the most product yield as well as methyl ester conversion can be reached within the values range from (70 to 75 %) and (88 to 90 %) respectively.